If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4x + 3) + -2(2 + -1x) = 2(2x + 3) + -5 Reorder the terms: -3(3 + 4x) + -2(2 + -1x) = 2(2x + 3) + -5 (3 * -3 + 4x * -3) + -2(2 + -1x) = 2(2x + 3) + -5 (-9 + -12x) + -2(2 + -1x) = 2(2x + 3) + -5 -9 + -12x + (2 * -2 + -1x * -2) = 2(2x + 3) + -5 -9 + -12x + (-4 + 2x) = 2(2x + 3) + -5 Reorder the terms: -9 + -4 + -12x + 2x = 2(2x + 3) + -5 Combine like terms: -9 + -4 = -13 -13 + -12x + 2x = 2(2x + 3) + -5 Combine like terms: -12x + 2x = -10x -13 + -10x = 2(2x + 3) + -5 Reorder the terms: -13 + -10x = 2(3 + 2x) + -5 -13 + -10x = (3 * 2 + 2x * 2) + -5 -13 + -10x = (6 + 4x) + -5 Reorder the terms: -13 + -10x = 6 + -5 + 4x Combine like terms: 6 + -5 = 1 -13 + -10x = 1 + 4x Solving -13 + -10x = 1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -13 + -10x + -4x = 1 + 4x + -4x Combine like terms: -10x + -4x = -14x -13 + -14x = 1 + 4x + -4x Combine like terms: 4x + -4x = 0 -13 + -14x = 1 + 0 -13 + -14x = 1 Add '13' to each side of the equation. -13 + 13 + -14x = 1 + 13 Combine like terms: -13 + 13 = 0 0 + -14x = 1 + 13 -14x = 1 + 13 Combine like terms: 1 + 13 = 14 -14x = 14 Divide each side by '-14'. x = -1 Simplifying x = -1
| 5v-2=-22 | | f(x)=6x^4-11x^3-3x^2+11x-3 | | 2(4k-2)-5(5k+1)=2-3(k+3) | | 36x^4-64x^2=L(6x^2+8x) | | 5x^2+34+45=0 | | 6(-y-3)=(1/3)(9-12y) | | x-8=9.49 | | 4x^3-9x^2-25x-12=0 | | x^3+6x^2+16x+96=0 | | 12d/14=16 | | 20-12X=64 | | (4x-5)(7x+3)= | | 48=9+3X | | (5)40+50x=400 | | x^3=-1331 | | 3y=-13 | | (4)32+5x=268 | | 5z+3/4=6z+1/4 | | 3/8x-9=15 | | a=1/2b-4 | | 5n-3(n+1)= | | 3*0+9y=10 | | -5(3n-3)-n= | | 4(1-4v)+3v= | | 15x^2+1-[4(x^2-8)+7]=0 | | 3(5x-4)+x= | | -5x-5(4-3x)= | | -3(1-2a)+5= | | x+8=0+2 | | 5(-4v-4)-3= | | 0+8=y+2 | | -2(-3-5b)-4b= |